Analysis of biophysical factors influencing nest site use by Sumatran orangutans (Pongo abelii) at the Ketambe Research Station, Gunung Leuser National Park - Ulfa Hansri Ar Rasyid; Erdiansyah Rahmi; Intan Padang; Ryan Moulana; Durrah Hayati; Yosie Syadza Kusuma (Global Forest Journal., 2026)
Nest-site use provides important insights into habitat quality and resource availability for Sumatran orangutans (Pongo abelii). This research investigated the biophysical characteristics of nesting habitats and evaluated the habitat variables associated with nest-site use at the Ketambe Research Station in Gunung Leuser National Park. Field data were collected using line transects and vegetation plots to document nest trees, food trees, and surrounding habitat characteristics. Vegetation composition was described, while multiple linear regression and Chi-square analyses were used to examine the relationships between habitat variables and nest occurrence. A total of 46 tree species (164 individuals) were recorded, with 64% identified as orangutan food trees. Multiple linear regression indicated that habitat biophysical factors significantly affected nest-site use (p = 0.006; R² = 0.583). Among these factors, only the distance to food trees was significantly associated with nest-site use (p = 0.023). The Chi-square test revealed a marginal association between nest occurrence and the presence of food trees (p = 0.087). These results indicate that proximity to food trees is the main factor influencing where orangutans build nests, underscoring the importance it maintaining food-tree resources for habitat management and conservation